2011
DOI: 10.1002/aic.12332
|View full text |Cite
|
Sign up to set email alerts
|

New efficient breadth‐first/level traversal tree search method for the design and upgrade of sensor networks

Abstract: This work studies the problem of optimally locating sensors for monitoring chemical processes, formally known as the sensor network design and upgrade problem. This problem is an integer programming problem and has been solved to global optimality only using tree search methods using depth-first strategy. In this article, we exploit certain cost properties of the different nodes in the tree to efficiently prune nonoptimal nodes using a breadth-first/level traversal tree search method to obtain the global optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…These problems include a revenue based term in the objective function. For such problems, the tree search algorithm loses its guarantee of global optimality. However, it is expected that the MICP version of these problems will yield global optimality and receive similar computational benefits from a GBD solution procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems include a revenue based term in the objective function. For such problems, the tree search algorithm loses its guarantee of global optimality. However, it is expected that the MICP version of these problems will yield global optimality and receive similar computational benefits from a GBD solution procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Since then a number of reformulations and solution procedures have been proposed to improve computational efficiency. The depth‐first tree search algorithm was extended to a breadth‐first/level‐traversal scheme . This method improved efficiency, but only for cases in which feasible solutions were found on the left side of the tree.…”
Section: Introductionmentioning
confidence: 99%
“…SNDP was formulated by Bagajewicz [1], and tackled by Nguyen and Bagajewicz [2] using a new tree search method that exploits certain cost properties of the different nodes in the tree to efficiently prune non optimal nodes using a breadth-first/level traversal tree search method to obtain the global optimum. Other approaches modeled the problem combining the integer and non-linear programming and solved it by means of depth-first or breadth-first tree searches.…”
Section: Introductionmentioning
confidence: 99%
“…Its solution has been tackle using exact and stochastic algorithms. Comprehensive reviews of these methods can be found elsewere. …”
Section: Introductionmentioning
confidence: 99%